Lateral Hypothalamic Orexin Neurons Mediate the Reward Effects of Pain Relief Induced by Electroacupuncture - Wang, Can; Chen, Meiyu; Qin, Chuan; Qu, Xiaoyi; Shen, Xueyong; Liu, Sheng (Frontiers in Molecular Neuroscience, 2022)
The reward of pain relief caused by acupuncture has been found to be clinically significant. However, the molecular mechanisms underlying acupuncture-induced reward of pain relief in chronic pain remains unclear and has not been analyzed in suitable preclinical models. Here, we determined whether acupuncture could potentially induce the reward of pain relief and orexin neuron signaling in the lateral hypothalamus (LH) exhibit a possible role in electroacupuncture (EA)-induced reward in spared nerve injury (SNI) rats. Therefore, by using conditioned place preference (CPP) paradigm, we noticed that EA induced the preference for cues associated with EA-induced pain relief at an early phase of chronic pain but not at late phase. These observations were different from the immediate anti-hyperalgesic effects of EA. c-Fos/Orexin double labeling revealed that EA stimulation on 14d but not on 28d after SNI modeling activated greater number of c-Fos positive orexin neurons in the LH after CPP test. Moreover, administration of orexin-A antagonist in the LH significantly blocked reward effects of pain relief induced by EA. Furthermore, by using cholera toxin b subunit combined with c-Fos detection, we found that orexin circuit from LH to the nucleus accumbens (NAc) shell were markedly activated after EA induced CPP. Microinjection of orexin antagonist into the NAc shell substantially attenuated CPP induced by EA. A combination of EA and low-dose orexin-A (intravenous injection) produced significantly more anti-hyperalgesia effects and CPP scores. Together, these findings clearly demonstrated that LH orexin signaling could potentially play a critical role in the reward effects of pain relief induced by acupuncture. The observations of the present study extended our understanding of LH orexin signaling on EA induced reward and provided new insights into mechanisms of acupuncture analgesia.